Experimental and DFT analysis of onion peels for its inhibition behavior against mild steel corrosion in chloride solutions - Jha V.K.; Chauhan M.S.; Pal S.; Jana S.; Ji G.; Prakash R. (My University, 2025)
Natural materials are good options for being used as inhibitors due to their high biodegradability, reasonable cost, easiness in use and high efficiency. In this regard, waste natural materials are very useful because they have all the properties of natural materials and easily available at very low cost (almost free). This work reports a similar kind of waste natural materials namely onion peels. The water extract of onion peels (WEOP) is characterized by UV–vis spectroscopy (UVS) and FTIR spectroscopy (FTIS). WEOP is tested for corrosion inhibition of mild steel (MS) in 1 M NaCl by various techniques like typical weight loss measurements (WLM), open circuit potential (OCP) curves, Tafel polarization (TP) curves, electrochemical impedance spectroscopy (EIS) and surface scanning microscopy (SEM). The maximum inhibition of mild steel corrosion is 90% (WLM). The reason of inhibition based on experimental analysis is proposed as adsorption of extract molecules on MS, which is found true in SEM images and Langmuir isotherm study. The WEOP is also examined by density functional theory principles, which recommends that the extract molecules can be easily adsorbed on MS and can stop corrosion of MS in NaCl solutions. Based on investigation, a schematic is introduced for compact explanation. © 2022 Indian Chemical Society